The Effect of Skill, Compensation and Placement toward Employee Performance in PT Gadai Syariah Berkat Bersama - Oktaviani, Dara Tri Yurindra; Arifin, Zainal; Daud, Ibrahim (Journal of International Conference Proceedings, 2023)
This research is to find out the effect of skill, compensation, and placement toward employee performance in PT Gadai Syariah Berkat Bersama. The research method is explanatory research. The sample of this study was 112 respondents and the sampling technique uses a saturated sampling with multiple linear regression using SPSS. The result of this study revealed that skill has an influence but a significant effect on employee performance, compensation has an influence but no significant impact toward employee performance and placement has an influence but no significant effect toward employee performance. While simultaneously skill, compensation, and placement have a significant effect toward employee performance in PT Gadai Syariah Berkat Bersama. Recommendation for further research to develop the research by replacing or adding other variables that could affect employee performance. Then PT Gadai Syariah Berkat Bersama can increase training and implement a reward and punishment system to increase motivation and discipline at work so that employees can provide their best for the company.Keywords: Skill, Placement, Compensation, Employee Performance